Medicalizing the Romantic Libido: Sexual Pleasure, Luxury, and the Public Sphere - Sha, Richard (Romanticism on the Net, 2003)
AbstractHabermas argues that in the eighteenth century, private vices were translated into public virtues; from the intimate spaces of the conjugal family came the public virtues of companionate love, voluntary association, and self-cultivation; from private commerce came acquisitiveness, competition, and rational calculation. This essay uses Habermas to reexamine Foucaultian histories of sexuality, arguing that the enormous medical literature on pleasure--luxury, sexual pleasure, masturbation, nerves--polices this transition from private vice to public virtue, but in sometimes surprising ways. The key was to explain why certain pleasurable experiences (acquisitiveness for its own sake and sexual intimacy outside the normative middle-class family) were not legitimately or even empirically pleasurable, despite potential somatic evidence to the contrary.